(untitled) (Journal of Current and Advance Medical Research, 2023)
Background: Hepatic encephalopathy is the most common and debilitating complication among the patients with cirrhosis. Electrolyte derangement is greatly related to recurrence and outcome of patients hospitalized with hepatic encephalopathy. Objective: This study was aimed to find out the association between these two variables in our setting. Methodology: The study was a cross-sectional study and conducted among 100 patients admitted with hepatic encephalopathy. Diagnosis and staging of hepatic encephalopathy were done based on West Haven staging, and severity of liver cirrhosis by the MELD (Model for End-Stage Liver Disease) scoring, and the outcomes were determined by the condition of the patients during discharge. Baseline serum electrolyte level was done for all the study participants. Results: Among 100 patients, male-female ratio was 7:3 with an average (standard deviation) age 56.25(±14.8) years. Most common causes of hepatic encephalopathy were infection (40.0%), gastrointestinal bleeding (30.0%), electrolyte abnormality (30.0%). Outcomes of hepatic encephalopathy were complete recovery (75.0%), needed ICU admission (15.0%) and death (10.0%). This study found no co-relation between baseline electrolyte and complete recovery of these patients and no association with the outcome of the patients. Conclusion: Baseline serum electrolyte have no significant influence on recovery of the patients with hepatic encephalopathy with liver cirrhosis. Journal of Current and Advance Medical Research, January 2023;10(1):41-46